2006
DOI: 10.1177/00343552060490020901
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of the Employer Openness Survey

Abstract: This study describes the four-phase process used in developing the Employer Openness Survey (EOS). The EOS is an 18-item instrument designed to measure the openness of employers to hiring, accommodating, and promoting workers with disabilities. During the first phase, the authors generated potential questions and pilot-tested them with employers. They then evaluated scoring criteria and construct validity in the second phase. In the third phase, the EOS was field-tested with employers, scoring criteria were fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…These findings also add to the research of Schur and Kruse (2006), who found that when employer cultures were categorized as those that were open to diversity and those that were closed, all workers, including people with disabilities, were significantly more satisfied with the working conditions in open cultures. Gilbride, Vandergoot, Golden, and Stensrud (2006) developed a survey instrument to differentiate between open and closed employers. It could be used to identify open and closed organizations so that people with disabilities could more easily identify where they did and did not want to work.…”
Section: Discussionmentioning
confidence: 99%
“…These findings also add to the research of Schur and Kruse (2006), who found that when employer cultures were categorized as those that were open to diversity and those that were closed, all workers, including people with disabilities, were significantly more satisfied with the working conditions in open cultures. Gilbride, Vandergoot, Golden, and Stensrud (2006) developed a survey instrument to differentiate between open and closed employers. It could be used to identify open and closed organizations so that people with disabilities could more easily identify where they did and did not want to work.…”
Section: Discussionmentioning
confidence: 99%
“…As predicted in both the theory of planned behavior and identity theory [58], workplace behavior is influenced by perceived norms and expectations [59]. Managers, compared to other employees, have a disproportionately greater ability to shape those norms in their companies [60]. Diversity training is most likely to be effective when upper-level management is directly involved in educating current employees on company diversity priorities [49,52].…”
Section: Participant Factorsmentioning
confidence: 99%
“…The goal of this study is to consider negative attitudes representing stereotypes and their effects on two aspects of employment: hiring people with a disability and providing them with work-related accommodations. Negative attitudes are often related with barriers to hiring (Thomas et al, 1993;Gilbride et al, 2000) and to workplace accommodations (Stone and Colella, 1996;Gilbride et al, 2006). A second goal of this study is to examine how attitudes about hiring and accommodation vary with disability.…”
mentioning
confidence: 98%